Ecologically based definition of seasons clarifies predator–prey interactions. Issue 2 (4th April 2012) - Basille, Mathieu; Fortin, Daniel; Dussault, Christian; Ouellet, Jean‐Pierre; Courtois, Réhaume
<x xml:space="preserve">Abstract</x> Species interactions within food webs are driven by multiple constraints, including those imposed by seasonal changes in the environment. Ecologically sound definitions of seasons may therefore be a prerequisite for clarifying predator prey interactions. Most studies define biological seasons based on fixed schedules or on temporal changes in a single movement measurement. We used a novel clustering approach based on homogeneous space‐use patterns of GPS‐collared animals to reveal 7 biological seasons for caribou Rangifer tarandus caribou, and 5 for both moose Alces alces and grey wolves Canis lupus interacting in a boreal ecosystem. Subsequent evaluation of niche overlap showed that, as predicted, wolves had a stronger spatio‐temporal connection with moose, its main prey, than with caribou. Movement constraints and limiting resource distributions similarly affected all species in some instances, but also caused temporal changes in the extent of niche overlap between wolves and its two prey. The risk that caribou faced was not only linked to the niche overlap with wolves, but also to the extent of wolf‐moose niche overlap during the same period. Food‐web properties emerged from the analysis, with temporal changes in relative niche overlap reflecting the strength of trophic interactions during the year. Our study demonstrates how the study of trophic interactions can benefit from comprehensive definitions of biological seasons.